JUDICIAL REVIEW OF EDUCATIONAL CRIMES IN HIGHER EDUCATION - Taufik Husni (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2020)
Cases of educational crimes that have occurred recently have greatly shaken the world of higher education in Indonesia, one of which is a case of plagiarism in the Postgraduate Program of Doctoral Program (S-3) at Jakarta State University, so the authors are interested in researching several cases in universities. The existence of criminal law with criminal and administrative sanctions is needed to overcome various forms of irregularities in the world of higher education. The purpose of this study is to find the problem of the law relating to higher education and the role of law enforcement officers in tackling the crime of education in universities. While the main problem is the problem of the effectiveness of the law of the Republic of Indonesia number 20 of 2003 concerning the national education system and the law of the Republic of Indonesia number 12 of 2012 concerning higher education, as well as the problem of the functions and roles of law enforcement officers in tackling criminal acts of education in universities. This thesis uses normative law and empirical law research. In processing and analyzing data, researchers used qualitative analysis methodology, assisted with descriptive research, beginning with juridical analysis, supported by the law approach. All data collected is processed by systematically compiling data. The results of the study found problems namely the ineffectiveness of the two laws on education mentioned above, many found maladministration, lack of functioning and role of law enforcement officials and lack of legal action from the Ministry of technology research and higher education R.I. in overcoming legal violations in universities.